Evaluation of Teller Services to Customers and Analysing Customer Satisfaction with Teller Services at BSI KCP Lauser - Hayat, Kumala; Daim Harahap, Rahmat (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
This study discusses the effect of service quality on customer satisfaction in Islamic banks. The purpose of this writing is to know what is customer satisfaction and service quality how to measure service quality, and what are the factors that cause customer satisfaction. This writing can also be seen how the relationship between service quality and customer satisfaction. In conducting research the author uses the literature study method, the author gets references from reliable sources. The results showed that all dimensions of service quality have a significant positive effect on customer satisfaction, which means that the better the quality of service ranging from physical evidence, responsive data, reliability, assurance and empathy provided by Islamic banking will be able to increase customer satisfaction and vice versa. Service is not just about providing services to customers, but also understanding customer needs and desires. A good service must start from understanding the needs and desires of customers, providing the right solution, always updating and improving services, listening to customer feedback, and always being balanced with competitive prices and satisfying product quality